Quantifying non‐breeding season occupancy patterns and the timing and drivers of autumn migration for a migratory songbird using Doppler radar. Issue 10 (14th January 2016) - Laughlin, Andrew J.; Sheldon, Daniel R.; Winkler, David W.; Taylor, Caz M.
Abstract : For seasonal migrants, non‐breeding regions can play different roles in the ecology of their annual cycles: as stopover habitat, overwintering habitat, or as a combination in which some individuals stop‐over and others over‐winter. Such functional variations can lead to variation in occupancy dynamics and migration phenology to these different regions. In this study, we used data from archived Doppler weather surveillance radar to compare site‐occupancy and movement dynamics of a migratory songbird (tree swallow Tachycineta bicolor ) between two non‐breeding areas: southeastern Louisiana and central peninsular Florida, USA. Specifically, in each area, we 1) quantified long‐term (1996–2012) non‐breeding season occupancy dynamics, 2) quantified variation in timing of autumn migration, and 3) tested which climate variables along their respective flyways were best correlated with variation in dates of arrival. Additionally, we cross‐validated the dynamics from archived radar with data from eBird, a large‐scale citizen science database that provides an independent measure of avian occupancy. We found strong and significant correlations between radar‐estimated and eBird‐estimated occupancy dynamics in both Louisiana and Florida. Long‐term Louisiana occupancy dynamics conformed to our hypothesis that this region acts as a combined stopover and overwintering region whereas Florida occupancy dynamics were akin to a traditional winter region. Arrival to Louisiana during the study period was much earlier and took place over a much shorter arrival window than did arrival to Florida, which showed much more gradual arrival over the course of several months. At both sites, annual variation in mean arrival date was best explained by the amount of precipitation along the lower portions of their respective migration flyways.